Foraging behaviour of top predators mediated by pollution of psychoactive pharmaceuticals and effects on ecosystem stability - Bláha, Martin; Grabicova, Katerina; Shaliutina, Olena; Kubec, Jan; Randák, Tomáš; Zlabek, Vladimir; Buřič, Miloš; Veselý, Lukáš (The Science of the total environment, 2019)
Although pharmaceuticals are recognized as a major threat to aquatic ecosystems worldwide, little is known about their ecological effect on aquatic biota and ecosystems. Drug-induced behaviour changes could have a substantial impact on consumer-resource interactions influencing stability of the community and ecosystem. We combined laboratory experiments and functional response modelling to investigate effects of real wastewater treatment plant (WWTP) effluent, as well as environmentally relevant concentrations of the antidepressants citalopram and opioid pain medication tramadol, on trophic interactions. Our biological system consisted of dragonfly Aeshna cyanea larvae as predator of common carp Cyprinus carpio fry. Exposure to WWTP effluent significantly increased A. cyanea maximum feeding rate, while those parameters in tramadol and citalopram-exposed larvae were significantly lower from unexposed control group. This suggested the potential of all tested pollutants to have an effect on consumer-resource equilibrium in aquatic ecosystems. While WWTP effluent strengthened interaction strength (IS) of consumer-resource interaction dynamics making the food web more vulnerable to fluctuation and destabilization, tramadol and citalopram could inhibit the potential oscillations of the consumer-resource system by weakening the IS. Similar studies to reveal the potential of pervasive pharmaceuticals to change of consumer-resource interactions dynamics are needed, especially when real WWTP effluent consisting of mixture of various pharmaceuticals displayed very different effect from single compounds tested.
Keywords: Nymph; Predatory Behavior; Functional response; WWTP; Food Chain; kapři; selektivní inhibitory zpětného vychytávání serotoninu; predátorské chování; Models, Biological; Tramadol; Predator-prey interaction; tramadol; Avoidance Learning; zvířata; citalopram; Wastewater; Selective Serotonin Reuptake Inhibitors; Carps; učení vyhýbat se; nymfa; vážky; Waste Water; Odonata; inhibitory zpětného vychytávání serotoninu a noradrenalinu; biologické modely; Water Pollutants, Chemical; odpadní voda; Animals; Serotonin and Noradrenaline Reuptake Inhibitors; Serotonin Uptake Inhibitors; potravní řetězec; chemické látky znečišťující vodu; Citalopram; Maximum feeding rate